The Profile of Interferon-ɣ and BCG Scar as an Immune Response Reflection in Children with Leprosy - Renata Mayangsari; Iskandar Zulkarnain; Trisniartami Setyaningrum (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Leprosy in children are commonly found in Madura, Indonesia. Bacillus Calmette-Guerin (BCG) vaccination and interferon--γ (IFN-γ) level associated with severity of leprosy. Purpose: To evaluate IFN-γ level and BCG scar due to leprosy in child. Methods: A descriptive observational cross sectional research, with leprosy in patients in Bangkalan, Madura as subjects. Subjects has been collected through consecutive sampling, then BCG scars were observed and blood vein samples were taken to measure IFN-γ level. Results: IFN-γ level were below normal range in almost all subjects. Mean level in patients with BCG scar (10,07 pg/ml) were higher than patients with non-scar (6,9 pg/ml). Seventy percents patients without BCG scar tend to be MB type based on percentage BCG scar due to type of leprosy. Conclusion: Immunity status as a result of BCG vaccination measured from IFN-γ level has many confounding factor. BCG vaccination seems to have an important role in severity of leprosy. Patients with BCG scar tend to be PB type. BCG vaccination can be benefits to make milder symptoms of leprosy.